A metal single atom electrocatalyst and preparation method thereof

By loading metal single atom cluster MClx on the matrix material and regulating the coordination environment using ultrasonic crushing treatment, the dispersion and stability of metal single atom electrocatalysts are solved, and high electrocatalytic performance and long life are achieved, which are suitable for a variety of purposes Metal elements and matrix materials, suitable for mass production.

CN116116441BActive Publication Date: 2024-12-17CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310204628.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2024-12-17
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

Metal single-atom electrocatalysts have problems with poor dispersion, poor stability and prone to agglomeration, and it is difficult to achieve high electrocatalytic performance when the metal load is small.

Method used

By loading metal single atom cluster MClx on the matrix material, the coordination environment is regulated by ultrasonic crushing treatment, and a highly dispersed metal single atom electrocatalyst is formed, suitable for a variety of metal elements and matrix materials.

Benefits of technology

It realizes excellent electrochemical performance, good dispersion and stability of metal single-atom electrocatalysts, has a long service life, and obtains high electrocatalytic performance under low metal loading, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116116441B_ABST
    Figure CN116116441B_ABST
Patent Text Reader

Abstract

The present invention relates to a metal single-atom electrocatalyst and a preparation method thereof. The metal single-atom electrocatalyst of the present invention comprises: a matrix material, and an atomic cluster represented by the following formula (1) supported on the matrix material: MCl x Formula (1), wherein M is a metal single atom selected from the group consisting of Pt, Au, Pd, Rh, Ir, Ru, Co, Ni, Fe, and Cu, Cl is a coordination element, x is the coordination number of the Cl element, and satisfies 0<x<6, wherein the content of the metal single atom is 0.01 to 10 mass % relative to the mass of the metal single atom electrocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal single-atom electrocatalyst and a preparation method thereof, and belongs to the technical field of material science and engineering. Background Art

[0002] At present, platinum-based electrocatalysts have become the mainstream electrocatalysts due to their good catalytic activity, near-zero hydrogen adsorption free energy, and low overpotential. However, with the gradual increase in demand, the high cost of traditional commercial Pt / C electrocatalysts is still one of the main reasons limiting their large-scale application. How to design economical and practical electrocatalysts without affecting the electrochemical performance of platinum-based electrocatalysts has become a research hotspot for many scholars.

[0003] For nano-electrocatalysts, the small size accompanied by a larger specific surface area can bring more active sites. Therefore, nano-sizing the active center is an effective means to obtain more active sites by reducing the size of the active center.

[0004] In recent years, the research on small-sized nano-electrocatalysts has attracted widespread attention, especially in the fields of atomic-level nano-electrocatalysts such as single-atom electrocatalysts (SACs) and atomic clusters (ACs), and many excellent results have been reported.

[0005] Wei et al. (Non-patent Document 1) developed a method to synthesize atomically dispersed Pt electrocatalysts by freezing photochemical reduction, in which the presence of ice lattices greatly restricted the diffusion of atoms during the reduction process, thereby hindering the nucleation process and obtaining atomic-level active sites.

[0006] Dong et al. (Non-patent Document 2) used N-type doped porous nanostructured carbon carriers to fix and disperse nanoparticles (NPs). This strategy can improve the agglomeration of active sites to a great extent. In addition, Non-patent Document 2 introduced heteroatom dopants such as nitrogen into the carbon carrier, which further improved the activity and stability of the supported electrocatalyst by improving the metal-carrier interaction.

[0007] N. Duane Loh et al. (Non-patent document 3) found that the process of metal ion reduction in aqueous solution is mainly divided into three steps: (1) differentiation of ion-rich phase and ion-poor phase; (2) formation of amorphous ACs from the ion-rich phase; (3) growth of amorphous nano ACs into nanocrystals. Therefore, in the process of generating and obtaining ACs and SACs, atomic diffusion and the formation of metal cores must be prevented.

[0008] In addition, another effective means to enhance the activity of electrocatalysts is to regulate the electronic structure of electrocatalysts by introducing heteroatoms without changing the basic composition of electrocatalysts.

[0009] Prior art literature

[0010] Non-patent literature:

[0011] Non-patent document 1: Wei et al., DOI: 10.1038 / s41467-017-01521-4

[0012] Non-patent document 2: Dong et al., DOI: 10.1002 / asia.202100438

[0013] Non-patent document 3: N. Duane Loh et al., DOI: 10.1038 / nchem.2618 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] However, SACs still have some defects. For example, the state of the particles is extremely active with high activity. Therefore, atomic-level electrocatalysts are prone to problems such as poor dispersion, poor stability, and easy agglomeration. Therefore, how to increase the metal loading of SACs electrocatalysts while ensuring that the active centers are still isolated atoms is an important challenge in the current research of SACs electrocatalysts. In addition, how to obtain high electrocatalytic performance that can be achieved by catalysts with high metal loadings while having low metal loadings is also an important challenge in the research of SACs electrocatalysts.

[0016] In view of the above problems, one object of the present invention is to provide a metal single-atom electrocatalyst with excellent electrochemical performance, good dispersibility, excellent stability and long service life.

[0017] Another object of the present invention is to provide a method for preparing metal single-atom electrocatalysts, which can quickly and efficiently prepare a large number of metal single-atom electrocatalysts, is applicable to a variety of metal elements and matrix materials, and has the advantages of simple operation process, simple process flow, and is suitable for large-scale production.

[0018] Solutions for solving problems

[0019] Through long-term research by the inventors, it is found that the above-mentioned method problems can be solved by implementing the following method scheme:

[0020] [1]. The present invention provides a metal single-atom electrocatalyst, comprising:

[0021] A base material, and an atomic cluster represented by the following formula (1) supported on the base material:

[0022] MCl xFormula (1)

[0023] in,

[0024] M is a metal single atom selected from the group consisting of Pt, Au, Pd, Rh, Ir, Ru, Co, Ni, Fe, and Cu,

[0025] Cl is a coordination element,

[0026] x is the coordination number of Cl element and satisfies 0<x<6,

[0027] The content of the metal single atom is 0.01 to 10% by mass, preferably 0.1 to 10% by mass, relative to the mass of the metal single atom electrocatalyst.

[0028] [2] The metal single-atom electrocatalyst according to [1], wherein the matrix material is one or more selected from the group consisting of conductive carbon black, ultrathin carbon film, graphene, carbon nanotubes, TiO2, zinc oxide, cerium oxide, aluminum oxide, silicon oxide, iron oxide, manganese oxide, and C3N4.

[0029] [3] The metal single-atom electrocatalyst according to [1] or [2], wherein the chemical valence state of the M element is +1 to +4.

[0030] [4] The metal single-atom electrocatalyst according to any one of [1] to [3], wherein the coordination bond length of the Cl element is

[0031] [5] The present invention also provides a method for preparing a metal single-atom electrocatalyst according to any one of [1] to [4], characterized in that the method comprises the following steps:

[0032] Step (1): mixing a metal salt solution with a matrix material to obtain a mixed solution, wherein the metal salt is a Cl-containing compound of a metal single atom M,

[0033] Step (2): subjecting the mixed solution to ultrasonic crushing treatment to obtain the metal single atom electrocatalyst.

[0034] [6] The preparation method according to [5], wherein the concentration of the metal salt in the metal salt solution is 0.001 to 200 mmol / L, preferably 0.01 to 150 mmol / L.

[0035] [7]. The preparation method according to [5] or [6], wherein the solvent in the metal salt solution is one or more selected from the group consisting of water, ethylene glycol, ethanol, tetraethylene glycol, dimethylformamide, and formaldehyde.

[0036] [8] The preparation method according to any one of [5] to [7], wherein the ultrasonic frequency of the ultrasonic crushing treatment is 1 to 100 kHz, preferably 15 to 98 kHz, and more preferably 25 kHz to 90 kHz.

[0037] [9] The method according to any one of [5] to [8], wherein the voltage of the ultrasonic crushing treatment is 500 to 1000 V, preferably 520 to 970 V, and more preferably 550 to 920 V.

[0038]

[10] The preparation method according to any one of [5] to [9], wherein the processing power of the ultrasonic treatment is 10 to 100%, preferably 20 to 100%; and the processing time of the ultrasonic treatment is 1 second to 30 hours, preferably 5 seconds to 24 hours.

[0039] Effects of the Invention

[0040] By implementing the above method, the present invention can achieve the following method effects:

[0041] The metal single-atom electrocatalyst of the present invention has a suitable coordination environment, and therefore has excellent electrochemical performance, good dispersibility, excellent stability, and long service life;

[0042] In addition, the platinum metal loading of commercial platinum-carbon (Pt / C) catalysts is usually 20% to 60% (by mass) to obtain good catalytic performance. The metal single-atom electrocatalyst of the present invention can obtain high electrocatalytic performance with a metal loading much less than that of commercial catalysts;

[0043] The preparation method of the metal single-atom electrocatalyst of the present invention obtains a catalyst with excellent catalytic performance by regulating the catalyst coordination environment, such as the type and number of coordinated atoms;

[0044] The preparation method of the present invention can rapidly and efficiently prepare a large number of metal single-atom electrocatalysts, is applicable to a variety of metal elements and matrix materials, and has the advantages of simple operation process, simple process flow, and is applicable to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a scanning transmission electron microscope image of the metal single atom electrocatalyst in which Pt single atoms are supported on conductive carbon black according to Example 1 of the present invention.

[0046] Figure 2 It is the energy spectrum diagram of the metal single-atom electrocatalyst in which the Pt single atom is supported on the conductive carbon black according to Example 1 of the present invention.

[0047] Figure 3The current density-potential curves of the electrocatalytic hydrogen production performance tests in 0.5 M sulfuric acid of the metal single-atom electrocatalyst in which the Pt single atom is supported on the conductive carbon black of Example 1 of the present invention, the commercial platinum-carbon (Pt / C) electrocatalyst of Comparative Example 1, the conductive carbon black matrix without metal single atom support of Comparative Example 2, and the platinum catalyst supported on the conductive carbon black matrix of Comparative Examples 3 and 4.

[0048] Figure 4 It is the current density-potential curve of the cyclic stability performance test of the metal single-atom electrocatalyst of Pt single atom supported on conductive carbon black in Example 1 of the present invention before and after 2000 voltammetric cycle tests in 0.5M sulfuric acid. DETAILED DESCRIPTION

[0049] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0050] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0051] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0052] In this specification, unless otherwise specified, "%" means mass percentage.

[0053] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0054] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0055] In this specification, the numerical range expressed using "numerical value XX to numerical value YY" means a range including the endpoint numerical values ​​XX and YY.

[0056] In this specification, the term "room temperature" refers to a temperature condition of 25°C.

[0057] First aspect

[0058] The first aspect of the present invention provides a metal single-atom electrocatalyst, which includes a matrix material, and an atomic cluster represented by the following formula (1) supported on the matrix material: MCl x Formula (1), wherein M is a metal element selected from the group consisting of Pt, Au, Pd, Rh, Ir, Ru, Co, Ni, Fe, and Cu, Cl is a coordination element, x is the coordination number of the Cl element, and 0<x<6 is satisfied, wherein the content of the metal single atom is 0.01 to 10 mass % relative to 100 mass % of the metal single atom electrocatalyst.

[0059] Through in-depth research by the inventors of the present invention, it is found that introducing heteroatoms into the electrocatalyst to regulate the electronic structure of the electrocatalyst without changing the basic composition of the electrocatalyst is an effective means to improve the activity of the electrocatalyst. In particular, for the SACs electrocatalyst of the present invention, its coordination environment will greatly affect its electronic structure and thus affect the catalytic performance.

[0060] In the present invention, by changing the coordination environment of the M metal, the density of electronic states of the outer orbit of the metal single atom is changed (for example, the unoccupied 5d orbit of Pt is increased), and the interaction between the 1s orbit of the H atom is enhanced, so that the metal single atom electrocatalyst has excellent electrochemical performance. x The single atom is loaded on the surface of the matrix material to form a metal single atom electrocatalyst. In the metal single atom electrocatalyst of the present invention, MCl x The single atoms are loaded on the surface of the base material in a highly dispersed form, and the single atoms do not aggregate, so the dispersion is good. In addition, the metal single atom electrocatalyst of the present invention also has the advantages of excellent stability and long service life.

[0061] <Atomic cluster of formula (1)>

[0062] In the present invention, the metal single atom electrocatalyst comprises an atomic cluster represented by formula (1):

[0063] MCl x Formula (1)

[0064] wherein M is any one metal element selected from the group consisting of Pt, Au, Pd, Rh, Ir, Ru, Co, Ni, Fe, and Cu,

[0065] Cl is a coordination element,

[0066] x is the coordination number of the Cl element, 0<x<6.

[0067] In the atomic cluster represented by formula (1), the coordination number x of Cl satisfies 0<x<6. When x is greater than 6, the coordination number does not decrease, and the coordination environment of the M element cannot be regulated. Therefore, the effect of improving the electrochemical performance of the single atom catalyst of the present invention cannot be achieved. On the other hand, in the present invention, the coordination number of Cl is not 0. When x is 0, the metal M atom does not contain a coordination element, does not have a coordination environment, and is in a single substance state, and the technical effects of improving electrochemical performance and good dispersibility cannot be achieved.

[0068] In some specific embodiments of the present invention, the coordination number x of Cl can be 1, 2, 3, 4, or 5. In some preferred embodiments of the present invention, the coordination number x of Cl is preferably 2-4.

[0069] Although only the coordination number of Cl is limited in this specification, since the metal M atom of the present invention is supported on a base material described later, there may also be a situation where the metal M coordinates with the base material. For example, when the base material is conductive carbon black, there may also be a situation where the metal M coordinates with C.

[0070] In some embodiments of the present invention, the chemical valence state of the M element in the metal single atom electrocatalyst can be +1 to +4. In some specific embodiments of the present invention, the chemical valence state of M can be +1, +2, +3, or +4. In some preferred embodiments of the present invention, the chemical valence state of M is preferably +1 to +3.

[0071] In some embodiments of the present invention, the coordination bond length of Cl of the coordination element in the metal single-atom electrocatalyst can be In some specific embodiments of the present invention, the coordination bond length of Cl can be or

[0072] <Base material>

[0073] In the present invention, the metal single-atom electrocatalyst comprises a base material, and the atomic cluster represented by formula (1) of the present invention is supported on the base material.

[0074] In the present invention, "load" may mean that the atomic cluster of formula (1) is present on the surface of the matrix material, for example, the atomic cluster of formula (1) may be adsorbed on the surface of the matrix material, or the atomic cluster of formula (1) may be embedded in the surface of the matrix material. In addition, the atomic cluster of formula (1) may be physically adsorbed on the surface of the matrix material, or may form a chemical bond with the surface of the matrix material. The atomic cluster of formula (1) may be uniformly dispersed on the surface of the matrix material, or may be dispersed on the surface of the matrix material in a non-uniform manner.

[0075] In some specific embodiments of the present invention, the matrix material is one or more selected from the group consisting of conductive carbon black, ultrathin carbon film, graphene, carbon nanotubes, TiO2, zinc oxide, cerium oxide, aluminum oxide, silicon oxide, iron oxide, manganese oxide, and C3N4.

[0076] In some specific embodiments of the present invention, the content of the metal single atom M in the metal single atom electrocatalyst is 0.01 to 10 mass%, preferably 0.1 to 10 mass%, relative to 100 mass% of the metal single atom electrocatalyst. In some specific embodiments of the present invention, the content of the metal M can be 0.01 mass%, 0.05 mass%, 0.1 mass%, 0.5 mass%, 1 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass%, 6 mass%, 7 mass%, 8 mass%, 9 mass%, 10 mass%, etc.

[0077] Second aspect

[0078] The second aspect of the present invention provides a method for preparing the metal single-atom electrocatalyst according to the first aspect of the present invention.

[0079] In the present invention, the metal single-atom electrocatalyst of the present invention can be obtained through a simple, safe and effective preparation process.

[0080] By the manufacturing method of the present invention, the compound of the metal M containing Cl as the raw material is subjected to a high energy input treatment in a short time, such as ultrasonic crushing treatment, so that the Cl coordinated with the metal M in the compound of the metal M is reduced, that is, the coordination number is reduced. By changing the coordination environment of the metal M, the density of electronic states of the outer orbit of the metal single atom is changed (for example, the unoccupied 5d orbit in Pt is increased), and its interaction with the 1s orbit of the H atom is enhanced, so that the metal single atom electrocatalyst has excellent electrochemical performance. Thereafter, MCl x The atomic clusters are loaded on the surface of the matrix material to form a metal single atom electrocatalyst. In the metal single atom electrocatalyst obtained by the preparation method, MCl xThe atomic clusters are loaded on the surface of the base material in a highly dispersed form, and the metal single atoms do not aggregate, so the dispersion is good. In addition, the metal single atom electrocatalyst prepared by the preparation method of the present invention also has the advantages of excellent stability and long service life.

[0081] The preparation method of the present invention comprises the following steps:

[0082] Step (1): mixing a metal salt solution with a matrix material to obtain a mixed solution, wherein the metal salt is a Cl-containing compound of a metal single atom M,

[0083] Step (2): subjecting the mixed solution to ultrasonic crushing treatment to obtain a metal single atom electrocatalyst.

[0084] In some specific embodiments of the present invention, in step (1), a metal salt of a metal element M selected from the group consisting of any one of Pt, Au, Pd, Rh, Ir, Ru, Co, Ni, Fe, and Cu is used to prepare a metal salt solution with a solvent.

[0085] In some specific embodiments of the present invention, in step (1), the solvent used to prepare the metal salt solution is selected from one or more of the group consisting of water, ethylene glycol, ethanol, tetraethylene glycol, dimethylformamide, and formaldehyde. In the case where the solvent used is a mixed solvent of water and at least one of the above-mentioned organic solvents, the volume concentration of the organic solvent is 1 to 99%, or the mass concentration of the organic solvent is 1 to 99%. In some specific embodiments of the present invention, the volume concentration of the organic solvent can be 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, etc. In some specific embodiments of the present invention, the mass concentration of the organic solvent can be 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, etc.

[0086] In some embodiments of the present invention, the concentration of the metal salt in the metal salt solution in step (1) is 0.001 to 200 mmol / L, preferably 0.01 to 150 mmol / L. In a specific embodiment of the present invention, the concentration of the metal salt can be 0.001 mmol / L, 0.005 mmol / L, 0.01 mmol / L, 0.05 mmol / L, 0.1 mmol / L, 1 mmol / L, 2 mmol / L, 3 mmol / L, 4 mmol / L, 5 mmol / L, 6 mmol / L, 7 mmol / L, 8 mmol / L, 9 mmol / L, 10 mmol / L, 20 mmol / L, 30 mmol / L, 40 mmol / L, 50 mmol / L, 60 mmol / L, 70 mmol / L, 80 mmol / L, 90 mmol / L, 100 mmol / L, 120 mmol / L, 150 mmol / L, 180 mmol / L, 200 mmol / L, etc.

[0087] In some embodiments of the present invention, in step (2), the metal salt solution prepared in step (1) is mixed with one or more matrix materials selected from the group consisting of conductive carbon black, ultrathin carbon film, graphene, carbon nanotubes, TiO2, zinc oxide, cerium oxide, aluminum oxide, silicon oxide, iron oxide, manganese oxide, and C3N4 to obtain a mixed solution.

[0088] In some embodiments of the present invention, in step (2), the mixed solution obtained as described above is subjected to ultrasonic crushing treatment, and the treatment is performed by high-frequency ultrasonic crushing treatment.

[0089] In some specific embodiments of the present invention, a high-frequency ultrasonic cell crusher is used to convert 200VAC, 50Hz single-phase electricity into alternating electric energy with an ultrasonic treatment frequency of about 1 to 100kHz and an ultrasonic treatment voltage of about 500 to 1000V through a frequency conversion device, and a vibration wave is generated with appropriate impedance and power to supply a large amount of energy to the mixed solution in a short time. According to the preparation method of the present invention, by changing the parameters of the above-mentioned ultrasonic crushing treatment, the coordination environment in the metal single-atom electrocatalyst is regulated, thereby obtaining the desired coordination number, chemical valence state and coordination bond length of the Cl element, so that the metal single-atom electrocatalyst of the present invention has excellent electrochemical performance, good dispersibility, excellent stability and long service life.

[0090] In some embodiments of the present invention, the frequency of the ultrasonic treatment can be 1 to 100 kHz, preferably 15 to 98 kHz, more preferably 25 kHz to 90 kHz. In some specific embodiments of the present invention, the frequency of the ultrasonic treatment can be 1 kHz, 5 kHz, 10 kHz, 15 kHz, 20 kHz, 25 kHz, 30 kHz, 35 kHz, 40 kHz, 45 kHz, 50 kHz, 55 kHz, 60 kHz, 65 kHz, 70 kHz, 75 kHz, 80 kHz, 85 kHz, 90 kHz, 95 kHz, 100 kHz, etc.

[0091] In some embodiments of the present invention, the voltage of the ultrasonic treatment may be 500 to 1000 V, preferably 520 to 970 V, more preferably 550 to 920 V. In some specific embodiments of the present invention, the voltage of the ultrasonic treatment may be 500 V, 520 V, 550 V, 600 V, 650 V, 700 V, 750 V, 800 V, 850 V, 900 V, 950 V, 1000 V, etc.

[0092] In some embodiments of the present invention, the power of the ultrasonic treatment can be 10-100%, preferably 20-100%. In some specific embodiments of the present invention, the power of the ultrasonic treatment can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, etc.

[0093] In some embodiments of the present invention, the ultrasonic treatment time is 1 second to 30 hours, preferably 5 seconds to 24 hours. In some specific embodiments of the present invention, the ultrasonic treatment time can be 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds, 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 20 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 30 hours, etc.

[0094] In some embodiments of the present invention, in step (2), after the mixed solution is subjected to the above-mentioned ultrasonic crushing treatment, it is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a constant temperature oven for drying to obtain a metal single-atom electrocatalyst including a metal single-atom electrocatalyst. During the drying process, the temperature of the constant temperature oven is controlled within the range of 40 to 80° C., and the drying time is 6 to 24 hours.

[0095] In some specific embodiments of the present invention, the drying temperature of the oven can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0096] In some specific embodiments of the present invention, the drying time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, etc.

[0097] In some specific embodiments of the present invention, the temperature of the constant temperature oven is controlled at 60° C., and the drying time is 12 hours.

[0098] The method for preparing the catalyst of the present invention obtains the metal single-atom electrocatalyst of the present invention through the above-mentioned steps (1) and (2), and can quickly and efficiently prepare a large number of metal single-atom electrocatalysts, is suitable for a variety of metal elements and matrix materials, and has the advantages of simple operation process, simple process flow, and is suitable for large-scale production.

[0099] Example

[0100] The present invention will be specifically described below based on Examples and Comparative Examples. However, the present invention is not limited to these Examples, etc. Unless otherwise specified, all "parts" and "%" used in Examples and Comparative Examples are based on mass.

[0101] Example 1

[0102] The metal single atom electrocatalysts were prepared by the following steps.

[0103] First, a metal salt solution is prepared, and a 15mmol / L chloroplatinic acid solution is prepared with chloroplatinic acid and deionized water. The prepared metal salt solution is mixed with conductive carbon black to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 50kHZ, a voltage of 600V, a treatment time of 1.5min, and a treatment power of 60%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h to obtain a Pt single atom electrocatalyst sample supported on conductive carbon black, wherein the content of the Pt metal single atom is 6% by mass. The coordination number of chlorine is 2, and the valence state of Pt is +2.

[0104] Comparative Example 1

[0105] A commercial platinum-carbon (Pt / C) catalyst with a platinum loading of 20 mass % was used as the catalyst sample of Comparative Example 1, and the current density-potential curve in 0.5 M sulfuric acid was tested as in Example 1. The results show that Figure 3 In. By Figure 3 It can be seen that the electrocatalytic hydrogen production performance of the Pt single atom electrocatalyst sample supported on conductive carbon black obtained in Example 1 of the present invention is better than that of the commercial platinum-carbon (Pt / C) catalyst.

[0106] Comparative Example 2

[0107] A conductive carbon black substrate without metal single atom loading was used as the catalyst sample of Comparative Example 2, and the current density-potential curve in 0.5 M sulfuric acid was tested in the same manner as in Example 1. The results show that Figure 3 In. By Figure 3 It can be seen that the electrocatalytic hydrogen production performance of the Pt single-atom electrocatalyst sample loaded on the conductive carbon black obtained in Example 1 of the present invention is better than that of the conductive carbon black.

[0108] Comparative Example 3

[0109] First, a metal salt solution was prepared, and a 15mmol / L chloroplatinic acid solution was prepared with chloroplatinic acid and deionized water. The prepared metal salt solution was mixed with conductive carbon black to obtain a mixed solution, and then the mixed solution was centrifuged and the supernatant was removed, and the residue was washed, and then the washed solid was placed in a 60°C constant temperature oven and dried for 12 hours to obtain a Pt single atom electrocatalyst sample supported on conductive carbon black. Among them, the content of Pt element is 7%, the coordination number of chlorine is 6, and the valence state of Pt is +6.

[0110] Comparative Example 4

[0111] First, a metal salt solution is prepared, and a 15mmol / L chloroplatinic acid solution is prepared with chloroplatinic acid and deionized water. The prepared metal salt solution is mixed with conductive carbon black to obtain a mixed solution, and then the mixed solution is centrifuged and the supernatant is removed. The residue is washed, and then the washed solid is placed in a 60°C constant temperature oven to dry for 12 hours, and the dried solid is placed in a tubular furnace with an argon atmosphere and sintered at 200°C to remove the chlorine element. Finally, a Pt single atom electrocatalyst sample loaded on conductive carbon black is obtained. Among them, the content of Pt single atoms is 4wt%, the coordination number of chlorine is 0, and the valence state of Pt is 0.

[0112] <Test methods and test results>

[0113] The Pt single-atom electrocatalyst sample loaded on the conductive carbon black obtained in Example 1 was observed using a scanning transmission electron microscope. Figure 1 In. By Figure 1 It can be seen that in the metal single-atom electrocatalyst sample obtained by the preparation method of the present invention, there are a large number of metal single atoms (such as Figure 1 ), and confirmed that no nanoparticles were generated.

[0114] The energy spectrum of C, Pt, and Cl elements of the Pt single-atom electrocatalyst sample loaded on conductive carbon black obtained in Example 1 was tested using transmission electron microscopy. The results are shown in Figure 2 In. By Figure 2 It can be seen that the metal single atoms prepared by the preparation method of the present invention are evenly distributed and have good dispersibility. In addition, the non-metallic element Cl is well introduced into the metal single atom electrocatalyst as the main coordination element.

[0115] The current density-potential curves of the catalyst samples obtained in Example 1 and Comparative Examples 1 to 4 were tested in 0.5M sulfuric acid. Figure 3 In. By Figure 3 It can be seen that the Pt single atom electrocatalyst sample supported on the conductive carbon black of the present invention shows a more excellent electrocatalytic hydrogen production performance compared with the catalyst samples of Comparative Examples 1 to 4.

[0116] In addition, the current density-potential curve of the cyclic stability performance test of the Pt single-atom electrocatalyst sample supported on the conductive carbon black obtained in Example 1 above before and after 2000 voltammetric cycle tests in 0.5M sulfuric acid was tested, and the results are shown in Figure 4 In. By Figure 4 It can be seen that the Pt single-atom electrocatalyst sample loaded on the conductive carbon black of the present invention still maintains a relatively high catalytic activity after 2000 volt-ampere cycle tests, and is more practical in the production process.

[0117] Example 2

[0118] First, a metal salt solution is prepared, and a 10mmol / L chloroplatinic acid solution is prepared with a mixed solvent of potassium chloroplatinate and deionized water and ethanol (wherein the mass fraction of ethanol is 8%), and the prepared metal salt solution is mixed with graphene to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 40KHZ, a voltage of 700V, a processing time of 30s, and a processing power of 20%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Pt single-atom electrocatalyst sample loaded on graphene is obtained, wherein the content of the Pt metal single atom is 1% by mass. The coordination number of chlorine is 4, and the valence state of Pt is +4.

[0119] Example 3

[0120] First, a metal salt solution is prepared, and a 50mmol / L chloroplatinic acid solution is prepared with a mixed solvent of sodium chloroplatinate, ultrapure water and dimethylformamide (wherein the volume concentration of dimethylformamide is 5%), and the prepared metal salt solution is mixed with manganese oxide to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 30KHZ, a voltage of 650V, a processing time of 1h, and a processing power of 30%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Pt single-atom electrocatalyst sample loaded on manganese oxide is obtained, wherein the content of the Pt metal single atom is 5% by mass. The coordination number of chlorine is 2, and the valence state of Pt is +2.

[0121] Example 4

[0122] First, a metal salt solution is prepared, and a 0.1mmol / L chloroauric acid solution is prepared with a mixed solvent of chloroauric acid and deionized water and ethanol (wherein the mass fraction of ethanol is 16%), and the prepared metal salt solution is mixed with mesoporous carbon to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 25KHZ, a voltage of 600V, a processing time of 10s, and a processing power of 70%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. An Au single-atom electrocatalyst sample loaded on mesoporous carbon is obtained, wherein the content of Au metal single atoms is 0.1% by mass. The coordination number of chlorine is 4, and the valence state of Au is +4.

[0123] Example 5

[0124] First, a metal salt solution is prepared, and a 20mmol / L potassium chloroaurate solution is prepared with a mixed solvent of potassium chloroaurate and deionized water and formaldehyde (wherein the volume concentration of formaldehyde is 2%), and the prepared metal salt solution is mixed with carbon nanowires to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 60KHZ, a voltage of 900V, a processing time of 1.5min, and a processing power of 80%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. An Au single-atom electrocatalyst sample loaded on carbon nanowires is obtained, wherein the content of Au metal single atoms is 3% by mass. The coordination number of chlorine is 2, and the valence state of Au is +2.

[0125] Example 6

[0126] First, a metal salt solution was prepared, and a 70 mmol / L sodium chloroaurate solution was prepared using a mixed solvent of sodium chloroaurate, ultrapure water and tetraethylene glycol (wherein the volume concentration of tetraethylene glycol was 5%), and the prepared metal salt solution was mixed with iron oxide to obtain a mixed solution, and then the mixed solution was subjected to high-frequency ultrasonic crushing treatment, with a frequency of 70 KHZ, a voltage of 520 V, a processing time of 3 h, and a processing power of 90%. Thereafter, the mixed solution was centrifuged and the supernatant was removed, the residue was washed, and then the washed solid was placed in a 60 ° C constant temperature oven and dried for 12 h. An Au single atom electrocatalyst sample loaded on iron oxide was obtained, wherein the content of Au metal single atoms was 7% by mass. The coordination number of chlorine was 3, and the valence state of Au was +3.

[0127] Example 7

[0128] First, a metal salt solution is prepared, and a mixed solvent of chloropalladic acid, ultrapure water and ethylene glycol (wherein the volume concentration of ethylene glycol is 1%) is used to prepare a 0.5mmol / L chloropalladic acid solution, and the prepared metal salt solution is mixed with conductive carbon black to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 40KHZ, a voltage of 670V, a processing time of 8s, and a processing power of 100%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Pd single-atom electrocatalyst sample loaded on conductive carbon black is obtained, wherein the content of Pd metal single atoms is 0.9% by mass. The coordination number of chlorine is 4, and the valence state of Pd is +4.

[0129] Example 8

[0130] First, a metal salt solution is prepared, and a 30mmol / L potassium chloropalladate solution is prepared with a mixed solvent of potassium chloropalladate, ultrapure water and dimethylformamide (wherein the volume concentration of dimethylformamide is 30%), and the prepared metal salt solution is mixed with TiO2 to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 30KHZ, a voltage of 850V, a processing time of 3min, and a processing power of 90%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Pd single-atom electrocatalyst sample loaded on TiO2 is obtained, wherein the content of the Pd metal single atom is 2% by mass. The coordination number of chlorine is 2, and the valence state of Pd is +2.

[0131] Example 9

[0132] First, a metal salt solution is prepared, and an 80 mmol / L sodium chloropalladate solution is prepared with sodium chloropalladate and deionized water. The prepared metal salt solution is mixed with zinc oxide to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 45KHZ, a voltage of 1000V, a treatment time of 5h, and a treatment power of 80%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Pd single-atom electrocatalyst sample loaded on zinc oxide is obtained, wherein the content of Pd metal single atoms is 8% by mass. The coordination number of chlorine is 3, and the valence state of Pd is +3.

[0133] Example 10

[0134] First, a metal salt solution is prepared, and a 0.5mmol / L chloroiridic acid solution is prepared with a mixed solvent of chloroiridic acid and deionized water and formaldehyde (wherein the volume concentration of formaldehyde is 60%), and the prepared metal salt solution is mixed with graphene to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 90KHZ, a voltage of 550V, a processing time of 12s, and a processing power of 70%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. An Ir single-atom electrocatalyst sample loaded on graphene is obtained, wherein the content of the Ir metal single atom is 0.35% by mass. The coordination number of chlorine is 5, and the valence state of Ir is +5.

[0135] Embodiment 11

[0136] First, a metal salt solution is prepared, and a 45mmol / L potassium chloroiridate solution is prepared with a mixed solvent of potassium chloroiridate and deionized water and ethanol (wherein the mass fraction of ethanol is 30%), and the prepared metal salt solution is mixed with cerium oxide to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 15KHZ, a voltage of 1000V, a processing time of 4.5min, and a processing power of 60%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. An Ir single-atom electrocatalyst sample loaded on cerium oxide is obtained, wherein the content of Ir metal single atoms is 4.2% by mass. The coordination number of chlorine is 2, and the valence state of Ir is +2.

[0137] Example 12

[0138] First, a metal salt solution is prepared, and a 92mmol / L sodium chloropalladate solution is prepared with a mixed solvent of sodium chloroiridate, ultrapure water and dimethylformamide (wherein the volume concentration of dimethylformamide is 3%), and the prepared metal salt solution is mixed with C3N4 to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 80KHZ, a voltage of 920V, a processing time of 12h, and a processing power of 30%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. An Ir single-atom electrocatalyst sample loaded on C3N4 is obtained, wherein the content of Ir metal single atoms is 8.2% by mass. The coordination number of chlorine is 3, and the valence state of Ir is +3.

[0139] Example 13

[0140] First, a metal salt solution is prepared, and a mixed solvent of ruthenic acid, ultrapure water and ethylene glycol (wherein the volume concentration of ethylene glycol is 6%) is used to prepare a 0.5mmol / L ruthenic acid solution, and the prepared metal salt solution is mixed with mesoporous carbon to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 38KHZ, a voltage of 860V, a processing time of 16s, and a processing power of 70%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Ru single-atom electrocatalyst sample loaded on mesoporous carbon is obtained, wherein the content of Ru metal single atoms is 0.19% by mass. The coordination number of chlorine is 3, and the valence state of Ru is +3.

[0141] Embodiment 14

[0142] First, a metal salt solution was prepared, potassium ruthenate and deionized water were used to prepare a 28mmol / L potassium ruthenate solution, the prepared metal salt solution was mixed with cerium oxide to obtain a mixed solution, and then the mixed solution was subjected to high-frequency ultrasonic crushing treatment, the frequency was 43KHZ, the voltage was 780V, the treatment time was 25min, and the treatment power was 80%. Thereafter, the mixed solution was centrifuged and the supernatant was removed, the residue was washed, and then the washed solid was placed in a 60°C constant temperature oven and dried for 12h. A Ru single-atom electrocatalyst sample loaded on cerium oxide was obtained, wherein the content of Ru metal single atoms was 6.7% by mass. The coordination number of chlorine is 2, and the valence state of Ru is +2.

[0143] Embodiment 15

[0144] First, a metal salt solution is prepared, and a 92mmol / L sodium chloroiridate solution is prepared with a mixed solvent of sodium chlororuthenate and deionized water and formaldehyde (wherein the volume concentration of formaldehyde is 30%), and the prepared metal salt solution is mixed with silicon oxide to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 68KHZ, a voltage of 870V, a processing time of 12h, and a processing power of 30%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Ru single-atom electrocatalyst sample loaded on silicon oxide is obtained, wherein the content of Ru metal single atoms is 8.2% by mass. The coordination number of chlorine is 3, and the valence state of Ru is +3.

[0145] Example 16

[0146] First, a metal salt solution is prepared, and a mixed solvent of potassium hexachlororhodiumate, ultrapure water and dimethylformamide (wherein the volume concentration of dimethylformamide is 8%) is used to prepare a 0.05mmol / L potassium hexachlororhodiumate solution, and the prepared metal salt solution is mixed with manganese oxide to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 87KHZ, a voltage of 830V, a processing time of 48s, and a processing power of 100%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Rh single-atom electrocatalyst sample loaded on manganese oxide is obtained, wherein the content of Rh metal single atoms is 0.25% by mass. The coordination number of chlorine is 3, and the valence state of Rh is +3.

[0147] Embodiment 17

[0148] First, a metal salt solution was prepared, and a 38 mmol / L sodium hexachlororhodium solution was prepared with sodium hexachlororhodium and deionized water. The prepared metal salt solution was mixed with iron oxide to obtain a mixed solution, and then the mixed solution was subjected to high-frequency ultrasonic crushing treatment, with a frequency of 79 KHZ, a voltage of 786 V, a treatment time of 45 min, and a treatment power of 30%. Thereafter, the mixed solution was centrifuged and the supernatant was removed, the residue was washed, and the washed solid was placed in a 60°C constant temperature oven and dried for 12 hours. A Rh single atom electrocatalyst sample supported on iron oxide was obtained, wherein the content of Rh metal single atoms was 3.9% by mass. The coordination number of chlorine was 2, and the valence state of Rh was +2.

[0149] Embodiment 18

[0150] First, a metal salt solution is prepared, and a mixed solvent of rhodium chloride and deionized water and ethanol (wherein the mass fraction of ethanol is 95%) is used to prepare an 88mmol / L rhodium chloride solution, and the prepared metal salt solution is mixed with an ultra-thin carbon film to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 87KHZ, a voltage of 650V, a processing time of 22h, and a processing power of 20%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Rh single-atom electrocatalyst sample loaded on an ultra-thin carbon film is obtained, wherein the content of the Rh metal single atom is 9.4% by mass. The coordination number of chlorine is 2, and the valence state of Rh is +2.

[0151] Embodiment 19

[0152] First, a metal salt solution was prepared, and a 75mmol / L ferric chloride solution was prepared with ferric chloride and deionized water. The prepared metal salt solution was mixed with alumina to obtain a mixed solution, and then the mixed solution was subjected to high-frequency ultrasonic crushing treatment, with a frequency of 56KHZ, a voltage of 970V, a treatment time of 14h, and a treatment power of 40%. Thereafter, the mixed solution was centrifuged and the supernatant was removed, the residue was washed, and the washed solid was placed in a 60°C constant temperature oven and dried for 12h. An Fe single atom electrocatalyst sample supported on alumina was obtained, wherein the content of Fe metal single atoms was 7.2% by mass. The coordination number of chlorine was 2, and the valence state of Fe was +2.

[0153] Embodiment 20

[0154] First, a metal salt solution is prepared, and a mixed solvent of cobalt chloride ultrapure water and ethylene glycol (wherein the volume concentration of ethylene glycol is 8%) is used to prepare a 62mmol / L cobalt chloride solution, and the prepared metal salt solution is mixed with manganese oxide to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 47KHZ, a voltage of 580V, a processing time of 19h, and a processing power of 50%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Co single-atom electrocatalyst sample loaded on manganese oxide is obtained, wherein the content of Co metal single atoms is 8.4% by mass. The coordination number of chlorine is 2, and the valence state of Co is +2.

[0155] Embodiment 21

[0156] First, a metal salt solution was prepared, and a nickel chloride solution of 53 mmol / L was prepared with nickel chloride and deionized water. The prepared metal salt solution was mixed with zinc oxide to obtain a mixed solution, and then the mixed solution was subjected to high-frequency ultrasonic crushing treatment, with a frequency of 98 KHZ, a voltage of 870 V, a treatment time of 24 hours, and a treatment power of 30%. Thereafter, the mixed solution was centrifuged and the supernatant was removed, the residue was washed, and the washed solid was placed in a 60°C constant temperature oven and dried for 12 hours. A Ni single-atom electrocatalyst sample loaded on zinc oxide was obtained, wherein the content of Ni metal single atoms was 9.8% by mass, the coordination number of chlorine was 2, and the valence state of Ni was +2.

[0157] Embodiment 22

[0158] First, a metal salt solution is prepared, and a 53mmol / L copper chloride solution is prepared with a mixed solvent of copper chloride and deionized water and ethanol (wherein the mass fraction of ethanol is 30%), and the prepared metal salt solution is mixed with carbon nanowires to obtain a mixed solution, and then the mixed solution is subjected to high-frequency ultrasonic crushing treatment, with a frequency of 87KHZ, a voltage of 700V, a treatment time of 16h, and a treatment power of 20%. Thereafter, the mixed solution is centrifuged and the supernatant is removed, the residue is washed, and then the washed solid is placed in a 60°C constant temperature oven and dried for 12h. A Cu single-atom electrocatalyst sample loaded on carbon nanowires is obtained, wherein the content of Cu metal single atoms is 6.9% by mass. The coordination number of chlorine is 2, and the valence state of Cu is +2.

[0159] The metal single atom catalyst samples loaded on the matrix material of Examples 2 to 22 were subjected to the same tests as in Example 1. The results showed that the performance of the metal single atom catalyst samples of Examples 2 to 22 were similar to those in Example 1, and no generation of nanoparticles was confirmed in Examples 2 to 22.

[0160] It can be seen from the above Examples 1 to 22 that a large number of metal single-atom electrocatalysts can be prepared quickly and efficiently using the preparation method of the present invention. The preparation method of the present invention is applicable to a variety of metal elements and matrix materials, and has the advantages of simple operation process, simple process flow, and suitability for large-scale production. On the other hand, the metal single-atom electrocatalyst prepared by the preparation method of the present invention has excellent electrochemical properties, good dispersibility, excellent stability, and long service life.

[0161] Industrial Applicability

[0162] The metal single-atom catalyst provided by the present invention can be used in the field of electrocatalysis and can be prepared and applied industrially.

Claims

1. A metal single atom electrocatalyst, It is characterized in that It includes: A base material, and an atomic cluster represented by the following formula (1) supported on the base material: MCl x Formula (1) in, M is a metal single atom selected from the group consisting of Pt, Au, Pd, Rh, Ru, Co, Ni, Fe, and Cu, Cl is a coordination element, x is the coordination number of Cl element and satisfies 0<x<6, The content of the metal single atom is 0.01 to 10% by mass relative to the mass of the metal single atom electrocatalyst. The matrix material is selected from conductive carbon black, ultrathin carbon film, graphene, carbon nanotubes, TiO 2 , zinc oxide, cerium oxide, aluminum oxide, silicon oxide, iron oxide, manganese oxide, C 3 N 4 One or more of the group consisting of The metal single-atom electrocatalyst is obtained by a preparation method comprising the following steps: Step (1): mixing a metal salt solution with a matrix material to obtain a mixed solution, wherein the metal salt is a Cl-containing compound of a metal single atom M, Step (2): subjecting the mixed solution to ultrasonic crushing treatment to obtain the metal single atom electrocatalyst, The ultrasonic wave frequency of the ultrasonic wave crushing treatment is 1-100kHz, and the voltage of the ultrasonic wave crushing treatment is 500-1000V.

2. The metal single atom electrocatalyst according to claim 1, in, The content of the metal single atom is 0.1 to 10 mass % relative to the mass of the metal single atom electrocatalyst.

3. The metal single atom electrocatalyst according to claim 1 or 2, in, The chemical valence state of the M element is +1 to +4.

4. The metal single atom electrocatalyst according to claim 1 or 2, in, The coordination bond length of the Cl element is 5. A method for preparing a metal single-atom electrocatalyst according to any one of claims 1 to 4, It is characterized in that The method comprises the following steps: Step (1): mixing a metal salt solution with a matrix material to obtain a mixed solution, wherein the metal salt is a Cl-containing compound of a metal single atom M, Step (2): subjecting the mixed solution to ultrasonic crushing treatment to obtain the metal single atom electrocatalyst, The ultrasonic wave frequency of the ultrasonic wave crushing treatment is 1-100kHz, and the voltage of the ultrasonic wave crushing treatment is 500-1000V.

6. The preparation method according to claim 5, in, The concentration of the metal salt in the metal salt solution is 0.001 to 200 mmol / L.

7. The preparation method according to claim 5, in, The concentration of the metal salt in the metal salt solution is 0.01 to 150 mmol / L.

8. The preparation method according to any one of claims 5 to 7, in, The solvent in the metal salt solution is one or more selected from the group consisting of water, ethylene glycol, ethanol, tetraethylene glycol, dimethylformamide, and formaldehyde.

9. The preparation method according to any one of claims 5 to 7, in, The ultrasonic wave frequency of the ultrasonic wave crushing treatment is 15 to 98 kHz.

10. The preparation method according to any one of claims 5 to 7, in, The ultrasonic wave frequency of the ultrasonic wave crushing treatment is 25 to 90 kHz.

11. The preparation method according to any one of claims 5 to 7, in, The voltage of ultrasonic crushing treatment is 520~970V.

12. The preparation method according to any one of claims 5 to 7, in, The voltage of ultrasonic crushing treatment is 550~920V.

13. The preparation method according to any one of claims 5 to 7, in, The processing power of the ultrasonic treatment is 10 to 100%.

14. The preparation method according to any one of claims 5 to 7, in, The processing power of the ultrasonic treatment is 20 to 100%.

15. The preparation method according to any one of claims 5 to 7, in, The treatment time of the ultrasonic treatment is 1 second to 30 hours.

16. The preparation method according to any one of claims 5 to 7, in, The treatment time of the ultrasonic treatment is 5 seconds to 24 hours.

Citation Information

Patent Citations

  • Monatomic noble metal catalyst prepared by ultrasonic assisted replacement reaction and method thereof

    CN107694592A

  • Atomically dispersed palladium-copper catalyst, preparation method and catalytic applications thereof

    CN109225253A

  • Method for preparing MXene supported noble metal catalyst by ultrasonic-assisted method

    CN111545229A

  • Supported palladium monatomic catalyst and application thereof in cinnamyl aldehyde selective hydrogenation

    CN112191246A

  • Preparation method of atomic-scale dispersed noble metal / carbon composite material

    CN114308025A